How Economically Weaker Section (EWS) Reservation Amendment Bill Nourishes Existing Reservation Policy In The Indian Context? A Study On Kerala Scenario (International Journal of Food and Nutritional Sciences, 2022)
The idea of a ‘caste-based reservation policy’ has often been resisted by dominant right-wing forces right from colonial times. One of the main criticism against cast based reservation policy-, is that it should not be cast-based, it should be ‘meritorious’ based or based on ‘economic status’ instead. 124th amendment on current reservation policy evokes a lot of attention in society as it is an effort to empower the impoverished and an attempt to uplift and bring equality between rich and poor. The recent law that provides 10 percent reservation for economically backward sections is said to benefit the poor among upper castes as well as some farming communities. In spite of there being criticisms against the current reservation system including the bill bringing about to sub-nationalism, encouraging inefficiency, etc., the government is less interested to touch this area because it is a sensitive issue and caste-based organized politics is so strong in India. Here the researcher makes an attempt to study the positives and negatives of this bill in the light of facts and enquire more about whether this bill could be a positive step towards a more meaningful reservation policy and lead to a more prosperous society or not.